A fábrica e a casa": configurações do trabalho na indústria calçadista de Nova Serrana/MG - Alessandro Gomes Enoque (2003)
The recent discussion upon the impacts of the productive restructuration process in the world of work has accentuated the role performed by a social group traditionally marginalized in official statistics. The domicile workers, or be, those individuals who perform their activities inside the scope of their own residence, are re-aquiering a spacefor long lost in social-economic literature. Working as freelances or disguised waged workers, these new professionals are, almostalways, related to conditions of precariousness and instability. To think of domicile labor only in terms of precarization takes us, nevertheless, to just a parcial vision of the problem. The objective of this text is measured exactly in contributing to a better comprehension of the universe of domicile labor. Having as fundamental basis variables related to the workers profile, practices of human resources, to work processes andpolitical action practices, it will be made a comparison between the configuration of work in industrial universe in relation to the domicile universe. In this sense, similarities and differences that may exist when comparing similar productive practices carried out in distinct places will be searched.